Circuitry Underlying Spectrotemporal Integration in the Auditory Midbrain - Yavuzoglu, Asuman (Society for Neuroscience, 2011)
Combination sensitivity in central auditory neurons is a form of spectrotemporal integration in which excitatory responses to sounds at one frequency are facilitated by sounds within a distinctly different frequency band. Combination-sensitive neurons respond selectively to acoustic elements of sonar echoes or social vocalizations. In mustached bats, this response property originates in high-frequency representations of the inferior colliculus (IC) and depends on low and high frequency-tuned glycinergic inputs. To identify the source of these inputs, we combined glycine immunohistochemistry with retrograde tract tracing. Tracers were deposited at high-frequency (>56 kHz), combination-sensitive recording sites in IC. Most glycine-immunopositive, retrogradely labeled cells were in ipsilateral ventral and intermediate nuclei of the lateral lemniscus (VNLL and INLL), with some double labeling in ipsilateral lateral and medial superior olivary nuclei (LSO and MSO). Generally, double-labeled cells were in expected high-frequency tonotopic areas, but some VNLL and INLL labeling appeared to be in low-frequency representations. To test whether these nuclei provide low frequency-tuned input to the high-frequency IC, we combined retrograde tracing from IC combination-sensitive sites with anterograde tracing from low frequency-tuned sites in the anteroventral cochlear nucleus (AVCN). Only VNLL and INLL contained retrogradely labeled cells near (≤50 μm) anterogradely labeled boutons. These cells likely receive excitatory low-frequency input from AVCN. Results suggest that combination-sensitive facilitation arises through convergence of high-frequency glycinergic inputs from VNLL, INLL, or MSO and low-frequency glycinergic inputs from VNLL or INLL. This work establishes an anatomical basis for spectrotemporal integration in the auditory midbrain and a functional role for monaural nuclei of the lateral lemniscus.